Towards precise defect control in layered oxide structures by using oxide molecular beam epitaxy - Baiutti, Federico; Christiani, Georg; Logvenov, Gennady (Beilstein Journal of Nanotechnology, 2014)
In this paper we present the atomic-layer-by-layer oxide molecular beam epitaxy (ALL-oxide MBE) which has been recently installed in the Max-Planck Institute for Solid State Research and we report on its present status, providing some examples that demonstrate its successful application in the synthesis of different layered oxides, with particular reference to superconducting La2CuO4 and insulator-to-metal La2−xSrxNiO4. We briefly review the ALL-oxide MBE technique and its unique capabilities in the deposition of atomically smooth single-crystal thin films of various complex oxides, artificial compounds and heterostructures, introducing our goal of pursuing a deep investigation of such systems with particular emphasis on structural defects, with the aim of tailoring their functional properties by precise defects control.
Keywords: artificial superlattices; complex oxides; defect chemistry; interface effects; molecular beam epitaxy